Teaching Hearing Perception: adapting to the needs of the school reality - Ruiz Palomo, Esther; Lara Ortega, Fernando; Santamaría Conde, Rosa María (Historia y Comunicación Social, 2014)
Universities must periodically review their curricula to meet the requirements of the society in which they are acting and adapt its training to the specific needs of the target group. With this premise and with reference to a series of studies conducted in our country, this paper is example of this adaptation, specifically applied to the area of development of hearing perception, based on the training needs expressed by the group of teachers in the elementary education in the city of Burgos.